Análise da aglomeração produtiva do setor cerâmico no estado do Espírito Santo - Pavan, Francisco Luiz Feu Rosa (2009)
Deep changes have been happening in industries due to some factors mainly resulted from the evolution on political, social, cultural, environmental and institutional areas. In Brasil, due to the great territorial extension, companies agglomerations,mainly the ones from local arrangements of small and medium companies must search for productive aglomeration inclusion, aiming innovation, development and knowledge. Because of this deep change in the productive system, it is possible to understand that clusters create a link between industry, government and educational institution, with reflections on the productive and social chain. This brings advantages for all the economic system. In this context, this work aims to analyze ceramic industries in the State of Espírito Santo and their relation with the environment. Research method will evolve study of indicators found in the literature, local visit, a form applied in the companies and analyze of reports about companies arrangement. As a result, this research has detected possible poles or ceramic industries arrangement and cleared the complexity level of the relation between companies, public sector and university.